S100A13-driven interaction between pancreatic adenocarcinoma cells and cancer-associated fibroblasts promotes tumor progression through calcium signaling - Liuyuan Xia; Xin Guo; Dong Lu; Yixin Jiang; Xiaohui Liang; Yiwen Shen; Jiayi Lin; Lijun Zhang; Hongzhuan Chen; Jinmei Jin; Xin Luan; Weidong Zhang (Cell Communication and Signaling)
Abstract Background Cancer-associated fibroblasts (CAFs) are key components of the pancreatic adenocarcinoma (PAAD) tumor microenvironment (TME), where they promote tumor progression and metastasis through immunosuppressive functions. Although significant progress has been made in understanding the crosstalk between cancer cells and CAFs, many underlying mechanisms remain unclear. Recent studies have highlighted the importance of calcium signaling in enhancing interactions between tumor cells and the surrounding stroma, with the S100 family of proteins serving as important regulators. While the roles of some S100 proteins have been extensively studied, others, such as S100A13, remain less well understood. Methods Bioinformatic analysis was employed to predict the pathogenic potential of CAFs and S100A13. Stable S100A13 knockdown CAFs were generated using a short hairpin RNA system. Cellular viability and apoptosis rates were evaluated through CCK-8 and flow cytometry tests, respectively. Additionally, the wound healing and migration assays were conducted to assess the invasive and metastatic capabilities. Transcriptome analysis was conducted to identify differential gene expression and associated signaling pathways in PAAD cells derived from an indirect culture system. Furthermore, the protumoral role of S100A13 in PAAD was further verified using both 3D bioprinting and cell line-based xenograft tumor models. Results In this study, we identified a strong association between S100A13, a calcium-binding protein, and CAFs in PAAD. Gene expression analysis revealed that S100A13 was highly expressed in CAFs and correlated with poor prognosis. Knockdown of S100A13 in CAFs reduced the metastatic potential of PAAD cells. In addition, S100A13 depletion impaired cell motility and calcium signaling pathways within the TME. Furthermore, silencing S100A13 in CAFs markedly slowed PAAD progression in both tumor spheroids and Balb/c nude mice. Conclusions Together, our findings underscore the critical role of CAFs-derived S100A13 in PAAD progression and suggest that targeting S100A13 may offer a promising therapeutic strategy for PAAD.